Phylogenetic Detection of Patho Genic Escherichia coli Isolated from Different Sources in Najaf Hospitals - Najm, Rusul; Mohammed, Jinan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The Aim: The training intended to quarantine bacteria Escherichia coli from urinary tract infection, wound, burns patients and investigating the genes ChuA, yjaA, TspE4.C2 of the phylogenetic groups. Study Design: 100 samples were collected from patients with urinary tract infection, wounds and burns, for a period from the twenty-seventh of July 2022 to the eleventh of December 2023, and after diagnosing the samples in the laboratory by means of selective media, the addition of the VITEK-2 compact. Place and Duration of Study: All samples collected from July to December 2023. Samples were cultured on a MacConkey and Eosin Methylene Blue agar (EMB) and VITEK2 compact. Methodology: A total of 100 sample from bacteria Escherichia coli sample Isolated from urine, wounds, burns Collected from several hospitals in city of Najaf included (Al-Sadr Teaching Hospital, Al-Najaf Teaching Hospital, Al-Furat Al-Awsat Hospital, Al-Hakim General Hospital, Al-Zahra Teaching Hospital, Burns Center, Public Health Laboratory). Results: The results showed that the incidence of urinary tract infection 91%, and wound was 7%, while burns was 2%. the genes ChuA, yjaA, TspE4.C2 of the phylogenetic groups isolates were investigated using the PCR technique. Conclusion: they were classified into four groups according to the presence or absence of these genes, so the results for group B1 was (44%), B2 (43%), D (12%), and A (1%).